Novel smart phone flexible printed circuit board and module prepared based on weldable silver paste

By using solderable low-temperature silver paste, the problems of high-temperature curing damage and soldering failure in flexible printed circuit boards for smartphones are solved, achieving a comprehensive performance improvement in high-density integration and dynamic bending, and providing a highly reliable and low-cost soldering solution.

CN121001267AActive Publication Date: 2025-11-21NANO TOP ELECTRONICS TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511282857.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-09
Publication Date
2025-11-21
Estimated Expiration
2045-09-09

AI Technical Summary

Technical Problem

现有技术在制备智能手机柔性印刷电路板时,存在高温固化温度损伤热敏感元件、焊盘焊接失效及纳米填料团聚导致的动态弯折失效问题,无法满足高密度集成和动态弯折的需求。

Method used

Weldable low-temperature silver paste is used, which contains conductive fillers, resin system, curing agent and modified nanomaterials. It forms a highly efficient and stable three-dimensional conductive network through ultra-low temperature curing, achieving high-density welding and dynamic bending performance. Modified carbon nanotubes and antimony tin oxide powder are used to improve conductivity and welding reliability.

Benefits of technology

Achieving comprehensive improvements in mechanical properties, electrical conductivity, and welding reliability at ultra-low temperatures meets the high integration and reliability requirements of smartphones, avoids damage to heat-sensitive components caused by high-temperature processes, and provides a highly reliable and low-cost welding solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005588002000000221
    Figure BDA0005588002000000221
  • Figure BDA0005588002000000231
    Figure BDA0005588002000000231
Patent Text Reader

Abstract

The invention discloses a novel smart phone flexible printed circuit board and module prepared based on weldable silver paste, and belongs to the technical field of electronic materials and devices, conductor patterns in the flexible printed circuit board comprise a main circuit pattern and an auxiliary function structure formed by weldable low-temperature silver paste, the curing temperature of the weldable low-temperature silver paste is 90-110 DEG C, and the weldable low-temperature silver paste comprises conductive filler, a polymer resin system, an ester solvent, a curing agent, a silane coupling agent, a polyamide wax thixotropic agent, a polysiloxane defoaming agent, modified carbon nanotubes, modified antimony tin oxide powder, modified ceramic filler and nano yttrium oxide. The macromolecular resin system comprises cardanol-based epoxy resin, hydrogenated bisphenol A epoxy resin and a polyacrylate-CTBN copolymer; the invention provides a solution suitable for high-density interconnection, micro jumper, dynamic bending compensation and direct packaging of a micro bonding pad of a smart phone, and solves the problems that elements are damaged by a high-temperature process, a pre-plating layer is needed for welding and high-density integration is needed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electronic materials and devices, and in particular to a novel flexible printed circuit board and module for smartphones based on solderable silver paste. Background Technology

[0002] Flexible printed circuit boards (PCBs), with their significant advantages of lightweight design, ultra-thin profile, and three-dimensional bending capability, have become core components for smartphones to achieve full-screen, foldable, and high-density module integration. Traditional smartphone PCBs face three extreme challenges: First, form factor adaptability: the hinge area of ​​a foldable screen needs to withstand dynamic bending (bending radius ≤ 2mm, bending life > 100,000 cycles), while the narrow bezels of full-screen displays (≤ 0.3mm) require PCB wiring density to be increased to line width / spacing ≤ 0.05mm; Second, functional integration: modules such as Mini LED backlights, ultrasonic fingerprint sensors, and 5G millimeter-wave antennas require direct soldering of micro-components onto the PCB, demanding pad sizes ≤ 30μm and high soldering strength; Third, thermal management limitations: heat-sensitive components such as OLED screens and lithium batteries (temperature resistance < 150℃) require strictly limited processing temperatures.

[0003] Therefore, when applying silver paste to the precision manufacturing of flexible printed circuit boards for smartphones, it is necessary to simultaneously meet the requirements of ultra-low temperature curing (<110℃) to protect heat-sensitive components, nanoscale printing precision to adapt to high-density integration, direct solderability to enable direct connection of Mini LEDs, and dynamic bending stability to support folded shapes. Summary of the Invention

[0004] The purpose of this invention is to provide a novel flexible printed circuit board and module for smartphones based on solderable silver paste. In order to break through the three major technical boundaries of high density, high reliability and low temperature manufacturing of smartphones, this invention aims to solve the problems existing in the prior art, overcome the defects of high temperature silver paste curing temperature damaging flexible substrates and heat-sensitive components, eliminate the increased cost of pre-plating gold and the risk of micro-pad soldering failure caused by the inability of general silver paste to be directly soldered, and solve the problems of dynamic bending failure and printing inaccuracy caused by the agglomeration of nanofillers.

[0005] To achieve the above objectives, the present invention provides the following solution:

[0006] This invention provides a novel flexible printed circuit board for smartphones based on solderable silver paste, comprising a flexible insulating substrate and a conductor pattern disposed on the substrate. The key feature is that the conductor pattern includes a main circuit pattern formed from rolled copper, and auxiliary functional structures formed by solderable low-temperature silver paste in local areas of the main circuit pattern. The auxiliary functional structures include at least one of a micro-jump wire region, a high-density pad region, and a dynamic bending compensation region. The curing temperature of the solderable low-temperature silver paste is 90℃~110℃. ℃; by mass parts, the above-mentioned solderable low-temperature silver paste contains 55 to 70 parts conductive filler, 10 to 20 parts polymer resin system, 20 to 35 parts ester solvent, 3 to 8 parts curing agent, 1 to 3 parts silane coupling agent, 0.5 to 2 parts polyamide wax thixotropic agent, 0.2 to 0.5 parts polysiloxane defoamer, 0.5 to 2 parts modified carbon nanotubes, 0.5 to 2 parts modified antimony tin oxide powder, 0.5 to 2 parts modified ceramic filler and 0.05 to 0.1 parts nano yttrium oxide;

[0007] The aforementioned polymer resin system comprises cashew phenolic epoxy resin, hydrogenated bisphenol A epoxy resin, and polyacrylate-carboxyl-terminated liquid nitrile rubber copolymer in a mass ratio of 1:(0.8~1.2):(0.3~0.6). The polyacrylate-carboxyl-terminated liquid nitrile rubber copolymer is abbreviated as polyacrylate-CTBN copolymer. The aforementioned conductive filler comprises silver nanowires, spherical silver powder with a D50 range of 0.5μm~0.8μm, and low-temperature alloy powder. The aforementioned low-temperature alloy powder is a low-temperature alloy powder with a D50 range of 5μm~10μm.

[0008] Specifically, the mass ratio of the above-mentioned conductive filler, including silver nanowires, spherical silver powder, and low-temperature alloy powder, is (1.0–2.0):1:(0.2–0.5); the specific surface area of ​​the above-mentioned silver nanowires is 30 m². 2 / g~60m 2 / g; the above-mentioned low-temperature alloy powder is Sn42Bi58; the specific surface area of ​​the above-mentioned spherical silver powder is 1.0m². 2 / g~2.5m 2 / g.

[0009] Specifically, the cashew phenol-based epoxy resin has an epoxy value of 0.45 eq / 100g to 0.55 eq / 100g and a viscosity of 10000 mPa·s to 20000 mPa·s at 25°C. The preparation method of the above-mentioned polyacrylate-CTBN copolymer is as follows: acrylate monomers and carboxyl-terminated liquid nitrile rubber are subjected to free radical polymerization at a mass ratio of (8 to 12):1 in the presence of benzoyl peroxide initiator at 60°C to 80°C for 4 to 6 hours to obtain the polyacrylate-CTBN copolymer. The carboxyl-terminated liquid nitrile rubber has a carboxyl group mass fraction of 0.4% to 0.6% and a number average molecular weight of 3000 Da to 5000 Da. The mass of the benzoyl peroxide initiator is 1.5% to 3.0% of the total mass of the acrylate monomers and the carboxyl-terminated liquid nitrile rubber.

[0010] More specifically, the curing agent is a polyether polyamine curing agent and an imidazole accelerator in a mass ratio of (5-7):1, wherein the imidazole accelerator is selected from any one of 2-methylimidazole, 2-ethyl-4-methylimidazole, or 1-cyanoethyl-2-phenylimidazole; the polyether polyamine curing agent is a linear polyether diamine; the silane coupling agent is a mixed coupling agent of KH-550 and KH-560 in a mass ratio of 1:(1.5-3), wherein KH-550 is γ-aminopropyltriethoxysilane, and KH-560 is γ-glycidoxypropyltrimethoxysilane; the polysiloxane defoamer is a non-silicone defoamer containing defoaming polysiloxane; and the ester solvent is selected from any one of diethylene glycol butyl ether acetate, ethylene glycol ethyl ether acetate, or butyl butyrate.

[0011] More specifically, the preparation method of the above-mentioned modified ceramic filler is as follows: boron nitride powder with a particle size of 0.1μm to 0.3μm is dispersed in anhydrous ethanol, and a mixed modifier consisting of silane coupling agent KH-560 and polydopamine in a mass ratio of 1:(1.5 to 2.5) is added. The mixture is ultrasonically stirred at 200W to 400W at 50℃ to 60℃ for 4h to 6h, filtered, and then calcined at 80℃ to 100℃ for 2h to 4h. The total mass of the mixed modifier is 3% to 5% of the boron nitride powder.

[0012] Furthermore, the aforementioned polyamide wax thixotropic agent is a polyamide wax formed by the condensation of plant fatty acids and dimer fatty acids with ethylenediamine. Before use, the aforementioned polyamide wax thixotropic agent needs to be activated. The specific operation of the activation treatment is as follows: add the polyamide wax to a mixed solvent of isopropanol and N-methylpyrrolidone with a volume ratio of 1:1.5 to 2.0, add aminopropanol, control the activation temperature at 40℃ to 50℃, the stirring speed at 100 r / min to 150 r / min, and activate for 15 min to 30 min; wherein, the mass ratio of polyamide wax, mixed solvent and aminopropanol is 1:(5 to 8):(0.05 to 0.1).

[0013] Furthermore, the preparation process of the above-mentioned modified carbon nanotubes, in parts by mass, is as follows:

[0014] A1. Electrolyte preparation: Disperse 15 parts of carbon nanotubes in 280 to 320 parts of 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid, add 5 to 10 parts of 4-aminophenyl diazonium salt as a functionalizing agent, and sonicate at 200W to 400W for 30 to 60 minutes to form a suspension electrolyte.

[0015] A2. Electrochemical treatment: Place the above electrolyte in an electrolytic cell, with a graphite rod as the anode and a platinum sheet as the cathode, and carry out the electrolytic reaction for 2 to 4 hours under a voltage of 3V to 5V and a stirring speed of 200r / min to 400r / min.

[0016] A3. Post-reaction treatment: After the reaction is completed, the black solid is obtained by filtration. The black solid is washed alternately by centrifugation with N,N-dimethylformamide and deionized water until the supernatant is colorless and transparent. The supernatant is then vacuum dried at 60℃~80℃ for 10h~14h to obtain the modified carbon nanotubes mentioned above.

[0017] Furthermore, the preparation process of the above-mentioned modified antimony tin oxide powder, in parts by mass, is as follows:

[0018] B1. Preparation of suspension: Disperse 10 parts of antimony tin oxide powder with an average particle size of 30nm to 70nm in 150 parts to 200 parts of deionized water, add 1 part to 2 parts of sodium dodecylbenzene sulfonate, and sonicate at 400W to 60W for 30min to 60min to prepare a suspension.

[0019] B2. In-situ polymerization: Add 1 to 3 parts of pyrrole monomer to the above suspension and stir for 25 to 35 minutes under ice-water bath conditions; add 5 parts of 5% to 10% ammonium persulfate aqueous solution dropwise, controlling the dropwise addition temperature at 2℃ to 4℃, and react for 6 to 8 hours.

[0020] B3. Post-reaction treatment: After the reaction is completed, filter the mixture and wash the filter cake repeatedly with deionized water and ethanol until the filtrate is colorless. Dry the filter cake under vacuum at 60℃~80℃ for 20h~28h, grind it and pass it through a 600-800 mesh sieve to obtain the above-mentioned modified antimony tin oxide powder.

[0021] Furthermore, the preparation method of the above-mentioned solderable low-temperature silver paste is as follows:

[0022] S1. Add ester solvent to the reactor, then add polymer resin system, stir at 60℃~80℃ until the resin dissolves, add silane coupling agent and polysiloxane defoamer, cool to room temperature, add curing agent, keep the solution temperature below 30℃, stir until all phases are completely dissolved and mixed to obtain carrier solution.

[0023] S2. Add polyamide wax thixotropic agent to the carrier solution and stir at room temperature to obtain mixed solution A;

[0024] S3. Add low-temperature alloy powder and modified ceramic filler to mixed solution A, and stir and mix at room temperature to obtain mixed solution B;

[0025] S4. Add the silver nanowires and spherical silver powder to the mixed solution B, then add the yttrium nano-oxide, and stir and mix at room temperature to obtain the mixed solution C;

[0026] S5. Add the modified carbon nanotubes and modified antimony tin oxide powder to the mixed solution C, stir and mix, and control the stirring temperature to not exceed 30℃ to obtain the mixed solution D;

[0027] S6. Transfer the mixed solution D to a three-roll mill. First, adjust the gap between the fast roller and the middle roller to 65μm-75μm and the gap between the middle roller and the slow roller to 25μm-35μm, and grind for 1-2 passes. Then, adjust the gap between the fast roller and the middle roller to 35μm-45μm and the gap between the middle roller and the slow roller to 5-15μm, and grind for another 1-2 passes. Grind for a total of 2-4 passes to obtain the ground silver paste.

[0028] S7. Transfer the ground silver paste to a vacuum stirring vessel and stir and mix it under a vacuum of ≤-0.095MPa. After stirring, encapsulate the silver paste to obtain the above-mentioned solderable low-temperature silver paste.

[0029] A smartphone backlight module, the key features of which include the aforementioned novel flexible printed circuit board for smartphones, and a Mini LED chip soldered onto a conductor pattern of the aforementioned circuit board using a low-temperature solder; the Mini LED chip is soldered onto a high-density pad area formed by the solderable low-temperature silver paste in the aforementioned conductor pattern; the Mini LED chip has a size of 20μm×40μm~50μm×100μm, the low-temperature solder used for soldering is Sn42Bi58, and the soldering process parameters are: peak temperature 125℃±2℃, reflow time 45s±5s.

[0030] The present invention discloses the following technical effects:

[0031] The solderable low-temperature silver paste and its application in flexible printed circuit boards and modules for smartphones provided by this invention, through the synergistic effect of its components, achieves a comprehensive improvement in mechanical properties, conductivity, high-frequency characteristics, and soldering reliability under ultra-low temperature curing conditions, perfectly meeting the stringent requirements of ultra-high integration and high reliability in smartphones. It has the following beneficial effects:

[0032] First, the silver paste of the present invention can be rapidly cured at ultra-low temperatures, effectively avoiding damage to heat-sensitive components such as OLED screens and lithium batteries inside smartphones caused by high-temperature processes. At the same time, the three-dimensional network structure of polyacrylate-CTBN copolymer formed after curing gives the silver paste circuit excellent dynamic bending resistance, fully meeting the reliability requirements of extremely small bending radius and ultra-long life of foldable screen phone hinge area.

[0033] Secondly, the silver paste of this invention constructs a highly efficient and stable three-dimensional conductive network through multi-scale compounding of silver nanowires, microsphere silver powder and low-temperature alloy powder, as well as the innovative application of electrochemically modified carbon nanotubes and polypyrrole-coated antimony tin oxide. It has low sheet resistance and an impedance change rate of <5% after rigorous temperature cycling at 10GHz, perfectly matching the extreme requirements of 5G mobile phone millimeter-wave antennas for transmission loss and ensuring the integrity of high-speed signals.

[0034] Third, the nano-yttrium oxide and fillers treated with specific modification processes introduced in this invention achieve ultra-uniform dispersion of the nanophase in the system without the use of traditional dispersants, and enable a highly active solderable layer to be directly formed on the cured surface of the silver paste. It achieves a strong metallurgical bond with Sn42Bi58 solder, with a welding shear strength as high as 8.5N, and the failure mode is mostly internal fracture at the solder joint, resulting in a welding yield close to 100%. This successfully eliminates the need for pre-plating gold / tin, providing a highly reliable and low-cost solution for direct chip mounting of modules such as smartphone cameras and Mini LED displays.

[0035] Fourth, this invention integrates ultra-low temperature curing, ultra-high flexibility, excellent high-frequency conductivity and direct solderability into one, providing a comprehensive solution suitable for high-density interconnection of smartphones, micro jumpers, dynamic bending compensation and direct packaging of micro pads. It effectively solves the problems of conductivity and reliability caused by high-temperature process damage to components, the need for pre-plating for soldering and high-density integration in existing technologies. Detailed Implementation

[0036] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0037] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0038] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0039] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0040] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0041] Example 1

[0042] This embodiment provides a novel flexible printed circuit board for smartphones based on solderable silver paste, comprising a flexible insulating substrate and a conductor pattern disposed on the substrate. The conductor pattern includes a main circuit pattern formed from rolled copper, and auxiliary functional structures formed by a solderable low-temperature silver paste sample 1 in a local area of ​​the main circuit pattern. In this embodiment, the auxiliary functional structures include a micro-jump wire area, a high-density pad area, and a dynamic bending compensation area.

[0043] By mass, the solderable low-temperature silver paste sample 1 of this embodiment contains: 63 parts conductive filler sample 1, 15 parts polymer resin system sample 1, 28 parts diethylene glycol butyl ether acetate, 5 parts curing agent sample 1, 2 parts silane coupling agent sample 1, 1 part polyamide wax thixotropic agent sample 1, 0.3 parts polysiloxane defoamer BYK-055, 1 part modified carbon nanotube sample 1, 1 part modified antimony tin oxide powder sample 1, 1 part modified ceramic filler sample 1, and 0.08 parts nano-yttrium oxide.

[0044] Conductive filler sample 1 contains: a specific surface area of ​​45 m² 2 Sample 1 consists of three materials: a silver nanowire sample (g), a spherical silver powder sample (D50 of 0.6 μm), and a Sn42Bi58 (D50 of 8 μm) low-temperature alloy powder sample (D50 of 8 μm). The mass ratio of the three samples is 1.5:1:0.3. The specific surface area of ​​the spherical silver powder sample is 2.1 m². 2 / g.

[0045] Sample 1 of the polymer resin system includes cashew nut shell epoxy resin sample 1, hydrogenated bisphenol A epoxy resin, and polyacrylate-CTBN copolymer sample 1 in a mass ratio of 1:1:0.4. The cashew nut shell epoxy resin sample 1 has an epoxy value of 0.50 eq / 100g and a viscosity of 15000 mPa·s at 25℃. The polyacrylate-CTBN copolymer sample 1 is prepared by reacting acrylate monomers and carboxyl-terminated liquid nitrile rubber in a mass ratio of 10:1 at 70℃ for 5 hours using a benzoyl peroxide initiator. The mass of the benzoyl peroxide initiator is 2.5% of the total mass of the acrylate monomers and the carboxyl-terminated liquid nitrile rubber. The carboxyl group mass fraction in the carboxyl-terminated liquid nitrile rubber sample 1 is 0.51%, and the number average molecular weight is 4000 Da.

[0046] Curing agent sample 1 is a polyether polyamine curing agent and an imidazole accelerator in a mass ratio of 6:1. The imidazole accelerator is a latent imidazole accelerator, specifically 2-methylimidazole; the polyether polyamine curing agent is a linear polyether diamine, specifically EDR-148.

[0047] Silane coupling agent sample 1 is a mixed coupling agent of KH-550 and KH-560 with a mass ratio of 1:2.

[0048] Polyamide wax thixotropic agent sample 1 is a polyamide wax sample 1, specifically PA-8800, formed by the condensation of plant fatty acids and dimer fatty acids with ethylenediamine. Before use, PA-8800 needs to be activated. The specific activation procedure is as follows: add PA-8800 to a mixed solvent of isopropanol and N-methylpyrrolidone with a volume ratio of 1:1.8, add aminopropanol, control the activation temperature at 45℃, the stirring speed at 120 r / min, and activate for 20 min; wherein, the mass ratio of PA-8800, mixed solvent and aminopropanol is 1:6:0.08.

[0049] The modified ceramic filler sample 1 was prepared by dispersing 1 part of boron nitride powder with a particle size of 0.2 μm in 8 parts of anhydrous ethanol, adding a mixed modifier consisting of silane coupling agent KH-560 and polydopamine in a mass ratio of 1:2, reacting with ultrasonic stirring at 300 W at 55℃ for 5 h, filtering, and then calcining at 90℃ for 3 h; wherein, the total mass of the mixed modifier is 4% of the boron nitride powder.

[0050] The preparation process of modified carbon nanotube sample 1, by mass parts, is as follows:

[0051] A1. Electrolyte preparation: 15 parts of carbon nanotubes were dispersed in 300 parts of 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid, and 8 parts of 4-aminophenyl diazonium salt were added as functionalizing reagent. The mixture was ultrasonically treated with 300W power for 45 minutes to form suspension electrolyte 1.

[0052] A2. Electrochemical treatment: Electrolyte 1 was placed in an electrolytic cell, with a graphite rod as the anode and a platinum sheet as the cathode, and the electrolysis reaction was carried out for 3 hours under a voltage of 4V and a stirring speed of 300r / min.

[0053] A3. Post-reaction treatment: After the reaction was completed, the black solid was obtained by filtration. The black solid was washed 5 times by alternating centrifugation with N,N-dimethylformamide and deionized water until the supernatant was colorless and transparent. The supernatant was dried under vacuum at 70℃ for 12h to obtain modified carbon nanotube sample 1.

[0054] The preparation process of modified antimony tin oxide powder sample 1, by mass parts, is as follows:

[0055] B1. Preparation of suspension: 10 parts of antimony tin oxide powder with an average particle size of 50 nm were dispersed in 180 parts of deionized water, and 1.5 parts of sodium dodecylbenzene sulfonate were added. The mixture was ultrasonically treated with 500 W power for 45 min to prepare suspension 1.

[0056] B2. In-situ polymerization: Add 2 parts of pyrrole monomer to the suspension 1 and stir for 30 min under ice-water bath conditions; add 5 parts of 8% ammonium persulfate aqueous solution dropwise, controlling the dropwise addition temperature at 3℃, and react for 7 h.

[0057] B3. Post-reaction treatment: After the reaction is completed, the filter cake is filtered and repeatedly washed with deionized water and ethanol until the filtrate is colorless. The filter cake is vacuum dried at 70°C for 24 hours, ground and passed through a 700-mesh sieve to obtain modified antimony tin oxide powder sample 1.

[0058] Using the above-mentioned raw materials, a solderable low-temperature silver paste sample 1 was prepared, specifically as follows:

[0059] S1. Add 28 parts of diethylene glycol butyl ether acetate to the reactor, then add 15 parts of polymer resin system sample 1. Stir at 70°C and 400 r / min for 30 min until the resin is completely dissolved. Add 2 parts of silane coupling agent sample 1 and 0.3 parts of polysiloxane defoamer BYK-055. Cool to room temperature, add 5 parts of curing agent sample 1, keep the solution temperature at 25°C, and stir until all phases are completely dissolved and mixed to obtain carrier solution 1.

[0060] S2. Add 1 part of activated polyamide wax thixotropic agent sample 1 to carrier solution 1, and stir at 500 r / min for 45 min at room temperature to obtain mixed solution A1.

[0061] S3. Add 6.75 parts of Sn42Bi58 low-temperature alloy powder sample 1 and 1 part of modified ceramic filler sample 1 to the mixed solution A1, and stir at 500 r / min for 45 min at room temperature to obtain mixed solution B1.

[0062] S4. Add 33.75 parts of nano-silver wire sample 1 and 22.5 parts of spherical silver powder sample 1 to the mixed solution B1, then add 0.08 parts of nano-yttrium oxide, and mix at room temperature at a speed of 1000 r / min for 80 min to obtain mixed solution C1.

[0063] S5. Add 1 part of modified carbon nanotube sample 1 and 1 part of modified antimony tin oxide powder sample 1 to the mixed solution C1, stir at 1200 r / min for 110 min, and control the stirring temperature at 25℃ to obtain mixed solution D1.

[0064] S6. Transfer the mixed solution D1 to a three-roll mill. First, adjust the gap between the fast roller and the middle roller to 70 μm and the gap between the middle roller and the slow roller to 30 μm and grind twice. Then, adjust the gap between the fast roller and the middle roller to 40 μm and the gap between the middle roller and the slow roller to 10 μm and grind once more. Grind a total of 3 times to obtain the ground silver paste sample 1.

[0065] S7. Transfer the ground silver paste sample 1 to a vacuum mixing vessel and stir at a speed of 40 r / min for 30 min under a vacuum of -0.100 MPa. After stirring, encapsulate the silver paste to obtain solderable low-temperature silver paste sample 1. The curing temperature of solderable low-temperature silver paste sample 1 is 105℃.

[0066] Example 2

[0067] This embodiment provides a novel flexible printed circuit board for smartphones based on solderable silver paste, comprising a flexible insulating substrate and conductor patterns disposed on the substrate. The conductor patterns include a main circuit pattern formed from rolled copper, and auxiliary functional structures formed by a solderable low-temperature silver paste sample 2 in a local area of ​​the main circuit pattern; in this embodiment, the auxiliary functional structures include micro-jump wire areas and high-density pad areas.

[0068] By mass, the solderable low-temperature silver paste sample 2 of this embodiment contains: 70 parts conductive filler sample 2, 10 parts polymer resin system sample 2, 20 parts ethylene glycol ethyl ether acetate, 8 parts curing agent sample 2, 1 part silane coupling agent sample 2, 0.5 parts polyamide wax thixotropic agent sample 2, 0.2 parts polysiloxane defoamer BYK-088, 0.5 parts modified carbon nanotube sample 2, 2 parts modified antimony tin oxide powder sample 2, 2 parts modified ceramic filler sample 2, and 0.05 parts nano-yttrium oxide.

[0069] Conductive filler sample 2 contains: a specific surface area of ​​30 m² 2 Sample 2 consists of three materials: silver nanowires (with a density of / g), spherical silver powder (with a D50 of 0.5μm), and Sn42Bi58 cryogenic alloy powder (with a D50 of 5μm). The mass ratio of these materials is 2.0:1:0.5. The specific surface area of ​​the spherical silver powder sample is 1.0 m². 2 / g.

[0070] Polymer resin system sample 2 includes cashew nut shell phenolic epoxy resin sample 2, hydrogenated bisphenol A epoxy resin, and polyacrylate-CTBN copolymer sample 2 with a mass ratio of 1:0.8:0.6. Among them, the cashew nut shell phenolic epoxy resin sample 2 has an epoxy value of 0.45 eq / 100g and a viscosity of 20000 mPa·s at 25℃. The specific preparation method of polyacrylate-CTBN copolymer sample 2 is as follows: acrylate monomer and carboxyl-terminated liquid nitrile rubber are subjected to free radical polymerization at 60℃ for 6h in the presence of benzoyl peroxide initiator at a mass ratio of 12:1 to obtain polyacrylate-CTBN copolymer sample 2. Among them, the mass of benzoyl peroxide initiator is 1.5% of the total mass of acrylate monomer and carboxyl-terminated liquid nitrile rubber. The carboxyl mass fraction of carboxyl-terminated liquid nitrile rubber sample 2 is 0.6%, and the number average molecular weight is 5000 Da.

[0071] Curing agent sample 2 is a polyether polyamine curing agent and an imidazole accelerator in a mass ratio of 7:1. The imidazole accelerator is 2-methylimidazole; the polyether polyamine curing agent is EDR-148.

[0072] Silane coupling agent sample 2 is a mixed coupling agent of KH-550 and KH-560 with a mass ratio of 1:3.

[0073] Polyamide wax thixotropic agent sample 2 is a polyamide wax sample 2 composed of plant fatty acids and dimer fatty acids condensed with ethylenediamine, specifically MT 6650. Before use, MT 6650 needs to be activated. The specific activation procedure is as follows: add MT 6650 to a mixed solvent of isopropanol and N-methylpyrrolidone with a volume ratio of 1:1.5, add aminopropanol, control the activation temperature at 50℃, the stirring speed at 100 r / min, and activate for 30 min; wherein, the mass ratio of MT 6650, mixed solvent and aminopropanol is 1:8:0.05.

[0074] The modified ceramic filler sample 2 was prepared by dispersing 1 part of boron nitride powder with a particle size of 0.1 μm in 9 parts of anhydrous ethanol, adding a mixed modifier composed of silane coupling agent KH-560 and polydopamine in a mass ratio of 1:1.5, reacting with ultrasonic stirring at 200 W at 60℃ for 4 h, filtering, and calcining at 100℃ for 2 h; wherein, the total mass of the mixed modifier is 3% of the boron nitride powder.

[0075] The preparation process of modified carbon nanotube sample 2, by mass parts, is as follows:

[0076] A1. Electrolyte preparation: 15 parts of carbon nanotubes were dispersed in 280 parts of 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid, and 5 parts of 4-aminophenyl diazonium salt were added as functionalizing reagent. The mixture was ultrasonically treated with 400W power for 30 minutes to form suspension electrolyte 2.

[0077] A2. Electrochemical treatment: Electrolyte 2 was placed in an electrolytic cell, with a graphite rod as the anode and a platinum sheet as the cathode, and the electrolysis reaction was carried out for 4 hours under a voltage of 3V and a stirring speed of 400r / min.

[0078] A3. Post-reaction treatment: After the reaction, the black solid was obtained by filtration. The black solid was washed 6 times by alternating centrifugation with N,N-dimethylformamide and deionized water until the supernatant was colorless and transparent. The supernatant was dried under vacuum at 80℃ for 10h to obtain modified carbon nanotube sample 2.

[0079] The preparation process of modified antimony tin oxide powder sample 2, by mass parts, is as follows:

[0080] B1. Preparation of suspension: 10 parts of antimony tin oxide powder with an average particle size of 70 nm were dispersed in 200 parts of deionized water, 2 parts of sodium dodecylbenzene sulfonate were added, and the mixture was ultrasonically treated with 400 W power for 30 min to prepare suspension 2.

[0081] B2. In-situ polymerization: Add 3 parts of pyrrole monomer to the suspension 1 and stir for 25 min under ice-water bath conditions; add 5 parts of 10% ammonium persulfate aqueous solution dropwise, controlling the dropwise addition temperature at 4°C, and react for 6 h.

[0082] B3. Post-reaction treatment: After the reaction is completed, the filter cake is filtered and repeatedly washed with deionized water and ethanol until the filtrate is colorless; the filter cake is vacuum dried at 80℃ for 20h, ground and passed through a 600-mesh sieve to obtain modified antimony tin oxide powder sample 2.

[0083] Using the above-mentioned raw materials and in the specified proportions, solderable low-temperature silver paste sample 2 was prepared, specifically as follows:

[0084] S1. Add 20 parts of ethylene glycol ethyl ether acetate to the reactor, then add 10 parts of polymer resin system sample 2. Stir at 60°C and 300 r / min for 40 min until the resin is completely dissolved. Add 1 part of silane coupling agent sample 2 and 0.2 parts of polysiloxane defoamer BYK-088. Cool to room temperature, add 8 parts of curing agent sample 2, keep the solution temperature at 30°C, and stir until all phases are completely dissolved and mixed to obtain carrier solution 2.

[0085] S2. Add 0.5 parts of activated polyamide wax thixotropic agent sample 2 to carrier solution 2, and stir at 600 r / min for 30 min at room temperature to obtain mixed solution A2.

[0086] S3. Add 10 parts of Sn42Bi58 low-temperature alloy powder sample 2 and 2 parts of modified ceramic filler sample 2 to the mixed solution A2, and stir at 600 r / min for 30 min at room temperature to obtain mixed solution B2.

[0087] S4. Add 40 parts of nano-silver wire sample 2 and 20 parts of spherical silver powder sample 2 to the mixed solution B2, then add 0.05 parts of nano-yttrium oxide, and mix at room temperature at a speed of 1500 r / min for 90 min to obtain mixed solution C2.

[0088] S5. Add 0.5 parts of modified carbon nanotube sample 2 and 2 parts of modified antimony tin oxide powder sample 2 to the mixed solution C2, stir at 1500 r / min for 90 min, and control the stirring temperature at 30℃ to obtain mixed solution D2.

[0089] S6. Transfer the mixed solution D2 to a three-roll mill. First, adjust the gap between the fast roller and the middle roller to 75 μm and the gap between the middle roller and the slow roller to 25 μm and grind once. Then, adjust the gap between the fast roller and the middle roller to 35 μm and the gap between the middle roller and the slow roller to 5 μm and grind once more. Grind a total of 2 times to obtain the ground silver paste sample 2.

[0090] S7. Transfer the ground silver paste sample 2 to a vacuum mixing vessel and stir at 50 r / min for 20 min under a vacuum of -0.095 MPa. After stirring, encapsulate the silver paste to obtain solderable low-temperature silver paste sample 2. The curing temperature of solderable low-temperature silver paste sample 2 is 110℃.

[0091] Example 3

[0092] This embodiment provides a novel flexible printed circuit board for smartphones based on solderable silver paste, comprising a flexible insulating substrate and a conductor pattern disposed on the substrate. The conductor pattern includes a main circuit pattern formed from rolled copper and an auxiliary functional structure formed by a solderable low-temperature silver paste sample 3 in a local area of ​​the main circuit pattern; the auxiliary functional structure in this embodiment includes a dynamic bending compensation region.

[0093] By mass, the solderable low-temperature silver paste sample 3 of this embodiment contains: 55 parts conductive filler sample 3, 20 parts polymer resin system sample 3, 35 parts butyl butyrate, 3 parts curing agent sample 3, 3 parts silane coupling agent sample 3, 2 parts polyamide wax thixotropic agent sample 3, 0.5 parts polysiloxane defoamer TEGO Flow300, 2 parts modified carbon nanotube sample 3, 0.5 parts modified antimony tin oxide powder sample 3, 0.5 parts modified ceramic filler sample 3, and 0.1 parts nano-yttrium oxide.

[0094] Conductive filler sample 3 contains: a specific surface area of ​​60 m² 2 Sample 3 consists of silver nanowires (with a density of / g), spherical silver powder (with a D50 of 0.8μm), and Sn42Bi58 cryogenic alloy powder (with a D50 of 10μm); the mass ratio of the three samples is 1:1:0.2; the specific surface area of ​​the spherical silver powder sample is 2.5m². 2 / g.

[0095] Polymer resin system sample 3 includes cashew nut shell phenolic epoxy resin sample 3, hydrogenated bisphenol A epoxy resin and polyacrylate-CTBN copolymer sample 3 with a mass ratio of 1:1.2:0.3; wherein, the cashew nut shell phenolic epoxy resin sample 3 has an epoxy value of 0.55 eq / 100g and a viscosity of 10000 mPa·s at 25℃; the specific preparation method of polyacrylate-CTBN copolymer sample 3 is as follows: acrylate monomer and carboxyl-terminated liquid nitrile rubber are subjected to free radical polymerization at 80℃ for 4h in the presence of benzoyl peroxide initiator to obtain polyacrylate-CTBN copolymer sample 3; wherein, the mass of benzoyl peroxide initiator is 3.0% of the total mass of acrylate monomer and carboxyl-terminated liquid nitrile rubber; the carboxyl mass fraction of carboxyl-terminated liquid nitrile rubber sample 3 is 0.4%, and the number average molecular weight is 3000 Da.

[0096] Curing agent sample 3 is a polyether polyamine curing agent and an imidazole accelerator in a mass ratio of 5:1. The imidazole accelerator is 2-methylimidazole, and the polyether polyamine curing agent is EDR-148.

[0097] Silane coupling agent sample 3 is a mixed coupling agent of KH-550 and KH-560 with a mass ratio of 1:1.5.

[0098] Polyamide wax thixotropic agent sample 3 is a polyamide wax sample 3 formed by the condensation of plant fatty acids and dimer fatty acids with ethylenediamine, specifically thixotropic agent 7500. Before use, thixotropic agent 7500 needs to be activated. The specific operation of the activation treatment is as follows: add thixotropic agent 7500 to a mixed solvent of isopropanol and N-methylpyrrolidone with a volume ratio of 1:2.0, add aminopropanol, control the activation temperature at 40℃, the stirring speed at 150r / min, and activate for 15min; wherein, the mass ratio of thixotropic agent 7500, mixed solvent and aminopropanol is 1:5:0.1.

[0099] The modified ceramic filler sample 3 was prepared by dispersing 1 part of boron nitride powder with a particle size of 0.3 μm in 7 parts of anhydrous ethanol, adding a mixed modifier consisting of silane coupling agent KH-560 and polydopamine in a mass ratio of 1:2.5, reacting with ultrasonic stirring at 400W at 50℃ for 6 hours, filtering, and then calcining at 80℃ for 4 hours; wherein, the total mass of the mixed modifier is 5% of the boron nitride powder.

[0100] The preparation process of modified carbon nanotube sample 3, by mass parts, is as follows:

[0101] A1. Electrolyte preparation: 15 parts of carbon nanotubes were dispersed in 320 parts of 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid, and 10 parts of 4-aminophenyl diazonium salt were added as functionalizing reagent. The mixture was ultrasonically treated with 200W power for 60 minutes to form suspension electrolyte 3.

[0102] A2. Electrochemical treatment: Electrolyte 3 is placed in an electrolytic cell, with a graphite rod as the anode and a platinum sheet as the cathode, and the electrolysis reaction is carried out for 2 hours under a voltage of 5V and a stirring speed of 200r / min.

[0103] A3. Post-reaction treatment: After the reaction was completed, the black solid was obtained by filtration. The black solid was washed four times by alternating centrifugation with N,N-dimethylformamide and deionized water until the supernatant was colorless and transparent. The supernatant was dried under vacuum at 60°C for 14 hours to obtain modified carbon nanotube sample 3.

[0104] The preparation process of modified antimony tin oxide powder sample 3, by mass parts, is as follows:

[0105] B1. Preparation of suspension: 10 parts of antimony tin oxide powder with an average particle size of 30 nm were dispersed in 150 parts of deionized water, 1 part of sodium dodecylbenzene sulfonate was added, and the mixture was ultrasonically treated with 600 W power for 60 min to prepare suspension 3.

[0106] B2. In-situ polymerization: Add 1 part of pyrrole monomer to the suspension 3 and stir for 35 min under ice-water bath conditions; add 5 parts of 5% ammonium persulfate aqueous solution dropwise, controlling the dropwise addition temperature at 2°C, and react for 8 h.

[0107] B3. Post-reaction treatment: After the reaction is completed, the filter cake is filtered and repeatedly washed with deionized water and ethanol until the filtrate is colorless. The filter cake is vacuum dried at 60°C for 28 hours, ground and passed through an 800-mesh sieve to obtain modified antimony tin oxide powder sample 3.

[0108] Using the above-mentioned raw materials and in the specified proportions, solderable low-temperature silver paste sample 3 was prepared, specifically as follows:

[0109] S1. Add 35 parts of butyl butyrate to the reactor, then add 20 parts of polymer resin system sample 3. Stir at 80℃ and 500r / min for 20min until the resin is completely dissolved. Add 3 parts of silane coupling agent sample 3 and 0.5 parts of polysiloxane defoamer TEGO Flow 300. Cool to room temperature, add 3 parts of curing agent sample 3, keep the solution temperature at 22℃, and stir until all phases are completely dissolved and mixed to obtain carrier solution 3.

[0110] S2. Add 2 parts of activated polyamide wax thixotropic agent sample 3 to carrier solution 3, and mix at room temperature and 400 r / min for 60 min to obtain mixed solution A3.

[0111] S3. Add 5 parts of Sn42Bi58 low-temperature alloy powder sample 3 and 0.5 parts of modified ceramic filler sample 3 to mixed solution A3, and stir at 400 r / min for 60 min at room temperature to obtain mixed solution B3.

[0112] S4. Add 25 parts of nano-silver wire sample 3 and 25 parts of spherical silver powder sample 3 to the mixed solution B3, then add 0.1 parts of nano-yttrium oxide, and stir at 1000 r / min for 150 min at room temperature to obtain mixed solution C3.

[0113] S5. Add 2 parts of modified carbon nanotube sample 3 and 0.5 parts of modified antimony tin oxide powder sample 3 to the mixed solution C3, stir at 1000 r / min for 150 min, and control the stirring temperature at 22℃ to obtain mixed solution D3.

[0114] S6. Transfer the mixed solution D3 to a three-roll mill. First, adjust the gap between the fast roller and the middle roller to 65 μm and the gap between the middle roller and the slow roller to 35 μm and grind twice. Then, adjust the gap between the fast roller and the middle roller to 25 μm and the gap between the middle roller and the slow roller to 15 μm and grind twice more. Grind a total of 4 times to obtain the ground silver paste sample 3.

[0115] S7. Transfer the ground silver paste sample 3 to a vacuum mixing vessel and stir at 30 r / min for 40 min under a vacuum of -0.102 MPa. After stirring, encapsulate the silver paste to obtain solderable low-temperature silver paste sample 3. The curing temperature of solderable low-temperature silver paste sample 3 is 90℃.

[0116] Example 4

[0117] This embodiment provides a smartphone backlight module, including a novel flexible printed circuit board for smartphones prepared according to Embodiment 1, and a Mini LED chip soldered onto a conductor pattern of the circuit board using a low-temperature solder. The Mini LED chip is soldered onto a high-density pad area formed by the solderable low-temperature silver paste in the conductor pattern. The Mini LED chip has a size of 20μm×40μm~50μm×100μm, and the low-temperature solder used for soldering is Sn42Bi58. The soldering process parameters are: peak temperature 125℃±2℃, reflow time 45s±5s.

[0118] Example 5

[0119] This embodiment provides a smartphone backlight module, including a novel flexible printed circuit board for smartphones prepared according to Embodiment 2, and a Mini LED chip soldered onto a conductor pattern on the circuit board using low-temperature solder. The Mini LED chip is soldered onto a high-density pad area formed by the solderable low-temperature silver paste in the conductor pattern. The Mini LED chip has a size of 20μm×40μm~50μm×100μm, and the low-temperature solder used for soldering is Sn42Bi58. The soldering process parameters are: peak temperature 125℃±2℃, reflow time 45s±5s.

[0120] Example 6

[0121] This embodiment provides a smartphone backlight module, including a novel flexible printed circuit board for smartphones prepared according to Embodiment 3, and a Mini LED chip soldered onto a conductor pattern on the circuit board using a low-temperature solder. The Mini LED chip is soldered onto a high-density pad area formed by the solderable low-temperature silver paste in the conductor pattern. The Mini LED chip has a size of 20μm×40μm~50μm×100μm, and the low-temperature solder used for soldering is Sn42Bi58. The soldering process parameters are: peak temperature 125℃±2℃, reflow time 45s±5s.

[0122] Comparative Example 1

[0123] This comparative example provides a novel flexible printed circuit board for smartphones based on solderable silver paste, comprising a flexible insulating substrate and conductor patterns disposed on the substrate. The conductor patterns include a main circuit pattern formed from rolled copper, and auxiliary functional structures formed in local areas of the main circuit pattern by solderable low-temperature silver paste reference 1. The auxiliary functional structures in this comparative example include micro-jump wire areas, high-density pad areas, and dynamic bending compensation areas.

[0124] By mass, the solderable low-temperature silver paste control 1 of this comparative example contains: 63 parts conductive filler sample 1, 15 parts polymer resin system control 1, 28 parts diethylene glycol butyl ether acetate, 5 parts curing agent sample 1, 2 parts silane coupling agent sample 1, 1 part polyamide wax thixotropic agent sample 1, 0.3 parts polysiloxane defoamer BYK-055, 1 part modified carbon nanotube sample 1, 1 part modified antimony tin oxide powder sample 1, 1 part modified ceramic filler sample 1, and 0.08 parts nano-yttrium oxide.

[0125] The polymer resin system reference standard 1 includes cashew phenolic epoxy resin sample 1, hydrogenated bisphenol A epoxy resin, and carboxyl-terminated liquid nitrile rubber used in Example 1, with a mass ratio of 1:1:0.4.

[0126] Using the above-mentioned raw materials, a solderable low-temperature silver paste reference standard 1 was prepared. The specific process was the same as in Example 1, except that the polymer resin system sample 1 was replaced with the polymer resin system reference standard 1. The curing temperature of the prepared solderable low-temperature silver paste reference standard 1 was 123°C.

[0127] Comparative Example 2

[0128] This comparative example provides a novel flexible printed circuit board for smartphones based on solderable silver paste, comprising a flexible insulating substrate and conductor patterns disposed on the substrate. The conductor patterns include a main circuit pattern formed from rolled copper, and auxiliary functional structures formed in local areas of the main circuit pattern by solderable low-temperature silver paste reference 2. The auxiliary functional structures in this comparative example include micro-jump wire areas, high-density pad areas, and dynamic bending compensation areas.

[0129] By mass, the solderable low-temperature silver paste control sample 1 of this comparative example comprises: 63 parts conductive filler sample 1, 15 parts polymer resin system sample 1, 28 parts diethylene glycol butyl ether acetate, 5 parts curing agent sample 1, 2 parts silane coupling agent sample 1, 1 part polyamide wax thixotropic agent sample 1, 0.3 parts polysiloxane defoamer BYK-055, 1 part modified carbon nanotube sample 1, 1 part modified antimony tin oxide powder sample 1, and 1 part modified ceramic filler sample 1.

[0130] Using the above-mentioned raw materials, a solderable low-temperature silver paste reference standard 1 was prepared. The specific process was the same as in Example 1, except that nano-yttrium oxide was not added in step S4. The curing temperature of the prepared solderable low-temperature silver paste reference standard 2 was 105°C.

[0131] Comparative Example 3

[0132] This comparative example provides a novel flexible printed circuit board for smartphones based on solderable silver paste, comprising a flexible insulating substrate and conductor patterns disposed on the substrate. The conductor patterns include a main circuit pattern formed from rolled copper, and auxiliary functional structures formed in local areas of the main circuit pattern by a solderable low-temperature silver paste reference sample 3. The auxiliary functional structures in this comparative example include micro-jump wire areas, high-density pad areas, and dynamic bending compensation areas.

[0133] By mass, the solderable low-temperature silver paste reference standard 3 of this comparative example contains: 63 parts conductive filler sample 1, 15 parts polymer resin system sample 1, 28 parts diethylene glycol butyl ether acetate, 5 parts curing agent sample 1, 2 parts silane coupling agent sample 1, 1 part polyamide wax thixotropic agent sample 1, 0.3 parts polysiloxane defoamer BYK-055, 1 part modified carbon nanotube reference standard 1, 1 part modified antimony tin oxide powder sample 1, 1 part modified ceramic filler sample 1, and 0.08 parts nano-yttrium oxide.

[0134] The preparation method of modified carbon nanotube reference standard 1 is as follows:

[0135] A1. Acidification treatment: 15 parts of carbon nanotubes were added to a mixed acid consisting of 300 parts of concentrated nitric acid and 120 parts of concentrated sulfuric acid. 3% of the carbon nanotubes were added to ferric nitrate nonahydrate. The mixture was refluxed at 110°C for 6 hours. After cooling, the mixture was filtered, washed with deionized water until neutral, and vacuum dried at 90°C for 18 hours to obtain the carboxylated carbon nanotube sample to be cleaned.

[0136] A2. Cleaning carboxylated carbon nanotubes: Disperse the carboxylated carbon nanotube sample to be cleaned in a 0.3 mol / L nitric acid solution and sonicate at 300 W at 50 °C for 30 min; filter, wash with deionized water until the conductivity of the filtrate decreases by <10 μS / cm, and dry to obtain the carboxylated carbon nanotube sample.

[0137] A3. Silanization modification: Take 10 parts of carboxylated carbon nanotube sample and disperse them in a mixed solution of 160 parts of ethanol and water with a volume ratio of ethanol to water of 1:1.0. Add 2 parts of KH-560 and react with ultrasonication at 300W power and stirring at 400r / min at 70℃ for 6h. After the reaction is completed, filter, wash 3 times with anhydrous ethanol, and dry to obtain silanized modified carbon nanotube sample.

[0138] A4. Supercritical treatment: Take 5 parts of silanized modified carbon nanotube sample, 150 parts of deionized water, and 15 parts of cocamidopropyl dimethylamine acetone and add them to a supercritical reactor. After sealing, introduce carbon dioxide to a pressure of 30 MPa and react at 75°C for 6 hours. After depressurization, add 5 parts of dodecyl dimethyl benzyl ammonium chloride and inject carbon dioxide to a pressure of 50 MPa. Stir at 300 r / min for 4 hours.

[0139] A5. After depressurization and separation, the sample was washed with deionized water and vacuum dried at 90°C for 8 hours to obtain modified carbon nanotube reference standard 1.

[0140] Using the above-mentioned raw materials, a solderable low-temperature silver paste reference standard 3 was prepared. The specific process was the same as in Example 1, except that modified carbon nanotube reference standard 1 was used instead of modified carbon nanotube sample 1. The curing temperature of the prepared solderable low-temperature silver paste reference standard 3 was 112℃.

[0141] Comparative Example 4

[0142] This comparative example provides a novel flexible printed circuit board for smartphones based on solderable silver paste, comprising a flexible insulating substrate and conductor patterns disposed on the substrate. The conductor patterns include a main circuit pattern formed from rolled copper, and auxiliary functional structures formed in local areas of the main circuit pattern by solderable low-temperature silver paste reference 4. The auxiliary functional structures in this comparative example include micro-jump wire areas, high-density pad areas, and dynamic bending compensation areas. By mass parts, the solderable low-temperature silver paste reference 4 of this comparative example comprises: 63 parts conductive filler sample 1, 15 parts polymer resin system sample 1, 28 parts diethylene glycol butyl ether acetate, 5 parts curing agent sample 1, 2 parts silane coupling agent sample 1, 1 part polyamide wax thixotropic agent sample 1, 0.3 parts polysiloxane defoamer BYK-055, 1 part modified carbon nanotube sample 1, 1 part modified antimony tin oxide powder reference 1, 1 part modified ceramic filler sample 1, and 0.08 parts nano-yttrium oxide.

[0143] The preparation method of modified antimony tin oxide powder reference standard 1 is as follows:

[0144] B1. Disperse 10 parts of antimony tin oxide powder with an average particle size of 50 nm in 110 parts of anhydrous ethanol, and sonicate at 300 W for 30 min to obtain a suspension.

[0145] B2. Add 1.5 parts of KH-560 and 0.5 parts of acetic acid to the suspension as catalysts, and stir the mixture at 400 r / min at 60°C for 4 h.

[0146] B3. After the reaction was completed, the mixture was centrifuged, washed four times with anhydrous ethanol, dried under vacuum at 80°C for 12 hours, ground, and passed through a 600-mesh sieve to obtain modified antimony tin oxide powder reference standard 1.

[0147] Using the above-mentioned raw materials, a solderable low-temperature silver paste reference standard 4 was prepared. The specific process was the same as in Example 1, except that modified antimony tin oxide powder reference standard 1 was used instead of modified antimony tin oxide powder sample 1. The curing temperature of the prepared solderable low-temperature silver paste reference standard 4 was 105℃.

[0148] Analysis and Testing

[0149] Flexible circuits were formed on polyimide (PI) substrates using screen printing equipment for solderable low-temperature silver paste samples 1–3 and solderable low-temperature silver paste controls 1–4. After curing at their respective curing temperatures for 30 minutes, mechanical and electrical properties were tested. The linewidth of the flexible circuit was 15 μm, the thickness of the PI substrate was 50 μm, and the thickness of the silver paste was 15 μm ± 2 μm.

[0150] I. Mechanical Performance Testing

[0151] Mechanical properties include adhesion test, flexural strength test and hardness test. The test results are shown in Table 1.

[0152] Adhesion was tested using a cross-cut adhesion test. After pulling with 3M 610 tape, the peeling level was evaluated (0 being the best and 5 being the worst). The test sample was placed in a humid heat environment of 85℃ / 85%RH for 72 hours for humid heat aging, and the peeling level after aging was evaluated (0 being the best and 5 being the worst).

[0153] Bending resistance test: The PI substrate with silver paste wires was bent 180° repeatedly at a bending radius of R=3mm using a dynamic bending tester at normal room temperature (26℃), high temperature of 80℃ and low temperature of -40℃. The resistance change was monitored in real time and the number of bends when the resistance change exceeded 10% was recorded.

[0154] Hardness was tested using a pencil hardness tester according to standard number ASTM D3363.

[0155] Table 1: Mechanical Performance Test Results

[0156]

[0157]

[0158] As shown in Table 1, the weldable low-temperature silver paste samples of this invention all exhibit excellent comprehensive performance. Among them, weldable low-temperature silver paste sample 1 shows the most outstanding performance, demonstrating a bending life of over 10,000 cycles under normal temperature, high temperature, and low temperature environments, far exceeding industry standards and fully meeting the needs of extreme dynamic bending scenarios such as the hinge area of ​​foldable screen mobile phones. After undergoing 85%RH / 85℃ humid heat aging, the adhesion of weldable low-temperature silver paste sample 1 still remained at grade 0 or 1, proving that the resin system used has outstanding aging resistance and interface stability. Weldable low-temperature silver paste control sample 1, because it uses non-copolymerized CTBN as a toughening agent, has far inferior compatibility and synergistic effect with epoxy resin compared to the polyacrylate-CTBN copolymer of this invention. This results in a significant decrease in its adhesion, aging resistance, and high and low temperature bending resistance, especially at high temperatures where the resin softens and the performance deteriorates sharply. The solderable low-temperature silver paste reference 2, lacking nano-yttrium oxide, exhibits slightly weaker curing density and interfacial bonding, resulting in a decrease in adhesion to grade 2 after hygrothermal aging, and slightly lower bending resistance compared to samples 1 and 2 of this invention. The solderable low-temperature silver paste reference 3 uses modified carbon nanotubes prepared using an unimproved process, which have poorer dispersibility and aspect ratio retention than the electrochemically modified carbon nanotubes of this invention. This leads to stress concentration points forming in the resin matrix, resulting in lower bending resistance and interfacial bonding compared to the samples of this invention. The solderable low-temperature silver paste reference 4 uses modified antimony tin oxide prepared using an unimproved process, whose nanoparticles are more prone to agglomeration and have weaker interfacial bonding with the resin than those of this invention. While its mechanical properties are superior to references 1 and 3, they are still inferior to the samples of this invention.

[0159] II. Conductivity Test

[0160] The sheet resistance of the cured silver paste conductors was measured using a four-probe tester. The results are shown in Table 2.

[0161] The sample under test was subjected to 50 temperature cycles at a frequency of 10 GHz, from -40 ℃ to 85 ℃, and the shift of the characteristic impedance (Z) was measured and expressed as ΔZ / Z to evaluate the high-frequency impedance stability. The results are shown in Table 2. ΔZ represents the absolute value of the maximum deviation between the characteristic impedance value measured at the same frequency (10 GHz) and the initial value Z0 after 50 temperature cycles; Z refers to the initial characteristic impedance value measured at room temperature and a frequency of 10 GHz.

[0162] Shear resistance (probe diameter 5μm) was measured at 100 points on a 30μm×30μm pad array. The relative standard deviation (RSD) was calculated to determine the conductivity uniformity of the micro pads. The results are shown in Table 2.

[0163] Table 2: Conductivity Test Results

[0164] Sample to be tested Shear resistance (mΩ / □) <![CDATA[High-frequency impedance stability (ΔZ / Z0, %)]]> RSD (%) Solderable low-temperature silver paste sample 1 3.5 3.8 1.2 Sample 2 of solderable low-temperature silver paste 4.2 4.5 1.8 3 samples of solderable low-temperature silver paste 5.8 5.2 2.5 Solderable low-temperature silver paste reference standard 1 5.5 12.7 8.5 Solderable low-temperature silver paste reference standard 2 4.5 7.2 4.0 Weldable Low-Temperature Silver Paste Reference Standard 3 7.9 15.3 7.8 Solderable low-temperature silver paste reference standard 4 6.3 9.6 6.4

[0165] As shown in Table 2, the solderable low-temperature silver paste samples of the present invention all exhibit low sheet resistance, excellent high-frequency stability, and extremely high micropad uniformity. Solderable low-temperature silver paste sample 1 has a sheet resistance as low as 3.5 mΩ / □, and its impedance change rate after rigorous temperature cycling at high frequencies is only 3.8%, perfectly matching the extreme requirements of 5G millimeter-wave mobile phone antennas for transmission loss; its micropad sheet resistance has a relative standard deviation as low as 1.2%, demonstrating the excellent dispersibility and film uniformity of the modified filler. Solderable low-temperature silver paste control 1, due to poor resin system compatibility and high internal stress after curing, may generate microcracks, resulting in a higher sheet resistance and poorer high-frequency stability and uniformity. Solderable low-temperature silver paste control 2 lacks the promoting effect of nano-yttrium oxide on sintering densification, resulting in slightly poorer conductivity, manifested as a higher sheet resistance than sample 1, and significantly inferior high-frequency stability and uniformity compared to the samples of the present invention. The solderable low-temperature silver paste control 3 used modified carbon nanotubes prepared with an unmodified process. Its dispersibility was slightly poor, and its conductivity was impaired, preventing it from forming a more efficient conductive network within the system. Instead, it became an insulating point, resulting in the worst sheet resistance and high-frequency stability among all samples. The solderable low-temperature silver paste control 4 used modified antimony tin oxide powder prepared with an unmodified process. Agglomeration was possible, preventing it from effectively reducing contact resistance, leading to a higher sheet resistance, and poorer high-frequency stability and uniformity.

[0166] III. Welding Performance Testing

[0167] On the silver-soldered pads, Sn42Bi58 low-temperature solder paste and Mini LED chips were mounted using a standard SMT reflow soldering process (peak temperature 125℃). 200 solder joints were observed, and the soldering yield (i.e., the percentage of solder joints without cold solder joints, false solder joints, or tombstoning) was calculated. A high-precision push-pull force tester (resolution 0.001N) was used to select 20 solder joints, raising the lower limit to 5.0N / mm. 2 The shear strength was tested, and the failure modes were recorded. The failure modes were divided into three categories: internal fracture of the solder joint, delamination of the silver paste-pad interface, and a mixed mode of both. The results are shown in Table 3.

[0168] Artificial sweat prepared according to ISO 3160-2 standard was applied to the surface of the solder pads and sprayed continuously at 35°C for 24 hours. The untreated sample was used as a comparison. The wetting and spreading area of ​​the solder on the solder pads was tested, and the wetting area decay rate was calculated. The results are shown in Table 3.

[0169] Table 3: Welding Performance Test Results

[0170] Sample to be tested Welding yield (%) Shear strength (N) Failure Mode Wetting area attenuation rate (%) Solderable low-temperature silver paste sample 1 99.9 8.5 Internal fracture of solder joint 2.1 Sample 2 of solderable low-temperature silver paste 99.5 7.8 Internal fracture of solder joint 3.8 3 samples of solderable low-temperature silver paste 98.2 6.5 Hybrid mode 5.2 Solderable low-temperature silver paste reference standard 1 92.4 4.8 Silver paste interface stripping 18.7 Solderable low-temperature silver paste reference standard 2 95.1 5.5 Hybrid mode 10.4 Weldable Low-Temperature Silver Paste Reference Standard 3 97.6 6.0 Hybrid mode 6.9 Solderable low-temperature silver paste reference standard 4 94.2 5.2 Silver paste interface stripping 12.6

[0171] As shown in Table 3, the solderable low-temperature silver paste samples of this invention all exhibit extremely high soldering yield, soldering strength, and excellent environmental durability. The soldering yield of solderable low-temperature silver paste samples 1 and 2 is close to 100%, and the failure mode for both is internal fracture of the solder joint, proving that the strength of the weld joint is far higher than the bonding strength between the silver paste and the substrate, achieving top-level reliability. After salt spray and sweat corrosion tests, the solder wetting area attenuation rate of solder samples 1 and 2 is extremely low, indicating that their solder pad surfaces have good resistance to environmental corrosion. Solderable low-temperature silver paste control 1 is prone to silver paste interface peeling under soldering thermal stress, resulting in poor soldering strength and corrosion resistance. Solderable low-temperature silver paste control 2 has insufficient silver paste layer density and weak resistance to corrosive media penetration, leading to a high wetting area attenuation rate. In solderable low-temperature silver paste control 3, the modified carbon nanotubes have slightly poor dispersion, which can cause certain defects on the silver paste surface. Some solder joints peel off from the interface, while others fracture internally, exhibiting a mixed-mode failure, resulting in decreased soldering strength and consistency. The modified antimony tin oxide powder in the solderable low-temperature silver paste reference 4 failed to effectively protect the solder pad surface, had only average corrosion resistance, and may have affected the flatness due to agglomerates, leading to a decrease in soldering yield and strength.

[0172] IV. Application Performance of New Smartphone Modules

[0173] The novel smartphone module samples prepared in Examples 4 to 6 were tested as follows:

[0174] 1. Dynamic Bending Reliability Test: The module was installed in a foldable screen testing machine and subjected to more than 200,000 reciprocating bends with a bending radius of R=1.5mm in environments of -20℃, room temperature, and 60℃. After the test, the circuit conductivity of all new smartphone module samples remained at 100% yield, the silver paste circuit showed no cracks or peeling, and the Mini LED display function was normal.

[0175] 2. Dual 85°C High Temperature and Humidity Electrical Test: The display module was powered on for 1000 hours under 85°C / 85%RH conditions. During and after the test, the brightness decay rate of all new smartphone module samples was <3%, the color coordinate offset Δxy was <0.005, and there were no LED flickering or dead LED phenomena, proving the long-term stability and reliability of the silver paste circuit under high temperature and humidity conditions.

[0176] 3. High-temperature thermal shock test: 1000 cycles of thermal shock were conducted at temperatures ranging from -40℃ to 125℃. After the test, no micro-cracks were observed at the solder joint interfaces of all new smartphone module samples, and the chip shear strength showed no decrease, meeting the stringent requirements of smartphones to withstand complex usage environments.

[0177] In summary, the solderable low-temperature silver paste samples prepared by this invention, especially Sample 1, successfully combine excellent mechanical properties, outstanding conductivity, and ultra-high solderability, exhibiting comprehensive performance far superior to various comparative examples. Building upon previous technologies, this invention innovatively employs a polyacrylate-CTBN copolymer resin system, introduces nano-yttrium oxide, and develops a novel process for electrochemically modified carbon nanotubes and conductive polymer-coated modified antimony-tin oxide powder. This results in significant performance improvements and comprehensive optimization, providing a more reliable solution for the application of core components in smartphones, particularly high-end foldable screen phones.

[0178] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A novel flexible printed circuit board for smartphones based on solderable silver paste, comprising a flexible insulating substrate and a conductor pattern disposed on the substrate, characterized in that, The conductor pattern includes a main circuit pattern formed of rolled copper and an auxiliary functional structure formed by solderable low-temperature silver paste in a local area of ​​the main circuit pattern; the auxiliary functional structure includes at least one of a micro jumper area, a high-density pad area, and a dynamic bending compensation area. The curing temperature of the solderable low-temperature silver paste is 90℃~110℃; by mass parts, the solderable low-temperature silver paste comprises 55 parts~70 parts conductive filler, 10 parts~20 parts polymer resin system, 20 parts~35 parts ester solvent, 3 parts~8 parts curing agent, 1 part~3 parts silane coupling agent, 0.5 parts~2 parts polyamide wax thixotropic agent, 0.2 parts~0.5 parts polysiloxane defoamer, 0.5 parts~2 parts modified carbon nanotubes, 0.5 parts~2 parts modified antimony tin oxide powder, 0.5 parts~2 parts modified ceramic filler, and 0.05 parts~0.1 parts nano yttrium oxide; The polymer resin system comprises cashew phenolic epoxy resin, hydrogenated bisphenol A epoxy resin, and polyacrylate-carboxyl-terminated liquid butadiene-acrylonitrile rubber copolymer in a mass ratio of 1:(0.8~1.2):(0.3~0.6); the conductive filler comprises silver nanowires, spherical silver powder with a D50 range of 0.5μm~0.8μm, and low-temperature alloy powder, wherein the low-temperature alloy powder has a D50 range of 5μm~10μm.

2. The novel flexible printed circuit board for smartphones according to claim 1, characterized in that, The mass ratio of silver nanowires, spherical silver powder, and low-temperature alloy powder in the conductive filler is (1.0–2.0):1:(0.2–0.5); the specific surface area of ​​the silver nanowires is 30 m². 2 / g~60m 2 / g; the low-temperature alloy powder is Sn42Bi58; the specific surface area of ​​the spherical silver powder is 1.0m². 2 / g~2.5m 2 / g.

3. The novel flexible printed circuit board for smartphones according to claim 1, characterized in that, The cashew phenol-based epoxy resin has an epoxy value of 0.45 eq / 100g to 0.55 eq / 100g and a viscosity of 10000 mPa·s to 20000 mPa·s at 25℃. The preparation method of the polyacrylate-carboxyl-terminated liquid nitrile rubber copolymer is as follows: acrylate monomers and carboxyl-terminated liquid nitrile rubber are subjected to a free radical polymerization reaction at 60℃ to 80℃ for 4h to 6h in the presence of a benzoyl peroxide initiator at a mass ratio of (8 to 12):1 to obtain the polyacrylate-CTBN copolymer. The carboxyl group mass fraction in the carboxyl-terminated liquid nitrile rubber is 0.4% to 0.6%, and the number average molecular weight is 3000 Da to 5000 Da. The mass of the benzoyl peroxide initiator is 1.5% to 3.0% of the total mass of the acrylate monomers and the carboxyl-terminated liquid nitrile rubber.

4. The novel flexible printed circuit board for smartphones according to claim 1, characterized in that, The curing agent is a polyether polyamine curing agent and an imidazole accelerator in a mass ratio of (5-7):1, wherein the imidazole accelerator is selected from any one of 2-methylimidazole, 2-ethyl-4-methylimidazole, or 1-cyanoethyl-2-phenylimidazole; the polyether polyamine curing agent is a linear polyether diamine; the silane coupling agent is a mixed coupling agent of KH-550 and KH-560 in a mass ratio of 1:(1.5-3); the polysiloxane defoamer is a non-silicone defoamer containing defoaming polysiloxane; and the ester solvent is selected from any one of diethylene glycol butyl ether acetate, ethylene glycol ethyl ether acetate, or butyl butyrate.

5. The novel flexible printed circuit board for smartphones according to claim 1, characterized in that, The modified ceramic filler is prepared by dispersing boron nitride powder with a particle size of 0.1 μm to 0.3 μm in anhydrous ethanol, adding a mixed modifier consisting of silane coupling agent KH-560 and polydopamine in a mass ratio of 1:(1.5 to 2.5), and ultrasonically stirring at 200 W to 400 W at 50 °C to 60 °C for 4 h to 6 h, filtering, and then calcining at 80 °C to 100 °C for 2 h to 4 h; wherein the total mass of the mixed modifier is 3% to 5% of the boron nitride powder.

6. The novel flexible printed circuit board for smartphones according to claim 1, characterized in that, The polyamide wax thixotropic agent is a polyamide wax formed by the condensation of plant fatty acids and dimer fatty acids with ethylenediamine. Before use, the polyamide wax thixotropic agent needs to be activated. The specific operation of the activation treatment is as follows: add the polyamide wax to a mixed solvent of isopropanol and N-methylpyrrolidone with a volume ratio of 1:1.5 to 2.0, add aminopropanol, control the activation temperature at 40℃ to 50℃, the stirring speed at 100 r / min to 150 r / min, and activate for 15 min to 30 min; wherein, the mass ratio of polyamide wax, mixed solvent and aminopropanol is 1:(5 to 8):(0.05 to 0.1).

7. The novel flexible printed circuit board for smartphones according to claim 1, characterized in that, The preparation process of the modified carbon nanotubes, by mass parts, is as follows: A1. Electrolyte preparation: Disperse 15 parts of carbon nanotubes in 280 to 320 parts of 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid, add 5 to 10 parts of 4-aminophenyl diazonium salt as a functionalizing agent, and sonicate at 200W to 400W for 30 to 60 minutes to form a suspension electrolyte. A2. Electrochemical treatment: The electrolyte is placed in an electrolytic cell, with a graphite rod as the anode and a platinum sheet as the cathode, and the electrolysis reaction is carried out for 2 to 4 hours under a voltage of 3V to 5V and a stirring speed of 200r / min to 400r / min. A3. Post-reaction treatment: After the reaction is completed, the black solid is obtained by filtration. The black solid is washed alternately by centrifugation with N,N-dimethylformamide and deionized water until the supernatant is colorless and transparent. The modified carbon nanotubes are obtained by vacuum drying at 60℃~80℃ for 10h~14h.

8. The novel flexible printed circuit board for smartphones according to claim 1, characterized in that, The preparation process of the modified antimony tin oxide powder, by mass parts, is as follows: B1. Preparation of suspension: Disperse 10 parts of antimony tin oxide powder with an average particle size of 30nm to 70nm in 150 parts to 200 parts of deionized water, add 1 part to 2 parts of sodium dodecylbenzene sulfonate, and sonicate at 400W to 60W for 30min to 60min to prepare a suspension. B2. In-situ polymerization: Add 1 to 3 parts of pyrrole monomer to the suspension and stir for 25 to 35 minutes under ice-water bath conditions; add 5 parts of 5% to 10% ammonium persulfate aqueous solution dropwise, controlling the dropwise addition temperature at 2°C to 4°C, and react for 6 to 8 hours. B3. Post-reaction treatment: After the reaction is completed, filter the mixture and wash the filter cake repeatedly with deionized water and ethanol until the filtrate is colorless. Dry the filter cake under vacuum at 60℃~80℃ for 20h~28h, grind it and pass it through a 600-800 mesh sieve to obtain the modified antimony tin oxide powder.

9. The novel flexible printed circuit board for smartphones according to claim 1, characterized in that, The method for preparing the solderable low-temperature silver paste is as follows: S1. Add ester solvent to the reactor, then add polymer resin system, stir at 60℃~80℃ until the resin dissolves, add silane coupling agent and polysiloxane defoamer, cool to room temperature, add curing agent, keep the solution temperature below 30℃, stir until all phases are completely dissolved and mixed to obtain carrier solution. S2. Add polyamide wax thixotropic agent to the carrier solution and stir at room temperature to obtain mixed solution A; S3. Add low-temperature alloy powder and modified ceramic filler to mixed solution A, and stir and mix at room temperature to obtain mixed solution B; S4. Add the silver nanowires and spherical silver powder to the mixed solution B, then add the yttrium nano-oxide, and stir and mix at room temperature to obtain the mixed solution C; S5. Add the modified carbon nanotubes and modified antimony tin oxide powder to the mixed solution C, stir and mix, and control the stirring temperature to not exceed 30℃ to obtain the mixed solution D; S6. Transfer the mixed solution D to a three-roll mill. First, adjust the gap between the fast roller and the middle roller to 65μm-75μm and the gap between the middle roller and the slow roller to 25μm-35μm, and grind for 1-2 passes. Then, adjust the gap between the fast roller and the middle roller to 35μm-45μm and the gap between the middle roller and the slow roller to 5-15μm, and grind for another 1-2 passes. Grind for a total of 2-4 passes to obtain the ground silver paste. S7. Transfer the ground silver paste to a vacuum stirring vessel and stir and mix it under a vacuum of ≤-0.095MPa. After stirring, encapsulate the silver paste to obtain the solderable low-temperature silver paste.

10. A smartphone backlight module, characterized in that, The invention includes a novel flexible printed circuit board for smartphones as described in any one of claims 1 to 9, and a Mini LED chip soldered onto a conductor pattern of the circuit board using a low-temperature solder; the Mini LED chip is soldered onto a high-density pad area formed by the solderable low-temperature silver paste in the conductor pattern; the Mini LED chip has a size of 20μm×40μm to 50μm×100μm, the low-temperature solder used for soldering is Sn42Bi58, and the soldering process parameters are: peak temperature 125℃±2℃, reflow time 45s±5s.

Citation Information

Patent Citations

  • High-conductivity welding-resistance type low-temperature silver paste and preparation method thereof

    CN108565041A

  • HJT low-temperature conductive silver paste containing silver nano short rods and preparation method of HJT low-temperature conductive silver paste

    CN116564579A

  • PI film Mini-LED keyboard silver paste and preparation method thereof

    CN118299102A

  • Antioxidant conductive silver paste for automobile glass and preparation method thereof

    CN119889760A